CARANO MINANGKABAU DALAM EKSPRESI KRIYA KAYU - Hasnul Fachri; Ahmad Bahrudin; Nofrial Nofrial (Relief : Journal of Craft, 2021)
The paper contains Carano as craft artwork that is expected to be a medium of communication with the audience considering how important the role of Carano in Minangkabau traditional processions is. The concept of creating this work is the source of the Minangkabau Carano ideas that are expressed in works of art. The theoretical basis used in the realization of this work is the theory of form, function, aesthetics, and methods in the process of creating this work using three stages, namely exploration, design, and embodiment. The materials used in making the work are surian wood and uses carving techniques. The works created are in the form of two-dimensional relief that takes the form of a full Carano and some are only partially, the work only has an aesthetic function.ABSTRAKMakalah ini memuat Carano sebagai karya seni kriya yang diharapkan dapat menjadi media komunikasi dengan khalayak mengingat betapa pentingnya peran Carano dalam prosesi adat Minangkabau. Konsep penciptaan karya ini merupakan sumber dari ide-ide Carano Minangkabau yang dituangkan dalam karya seni rupa. Landasan teori yang digunakan dalam realisasi karya ini adalah teori bentuk, fungsi, estetika, dan metode dalam proses penciptaan karya ini menggunakan tiga tahapan yaitu eksplorasi, perancangan, dan perwujudan. Bahan yang digunakan dalam pembuatan karya tersebut adalah kayu surian dan menggunakan teknik ukir. Karya yang diciptakan berupa relief dua dimensi yang berbentuk Carano utuh dan ada pula yang hanya sebagian, karya tersebut hanya memiliki fungsi estetika.